Cancer immunology and melanoma immunotherapy - Rudinei Diogo Marques Linck; Rômulo Leopoldo de Paula Costa; Bernardo Garicochea (Sociedade Brasileira de Dermatologia, 2017)
Abstract: The stimulation of the immune system, in order to generate an attack against cancer cells, similarly to that which occurs in infectious disease, has long been matter of interest in oncology; however, only limited success has been achieved, with different treatment strategies tested in recent years. The development of new immune checkpoint inhibitors is currently changing this scenario, and immunotherapy is becoming a real choice among traditional cytotoxic treatments to fight cancer. Recent reports have shown efficacy and safety with the use of pembrolizumab, nivolumab, and ipilimumab for the treatment of different neoplasms, especially melanoma. In this article, we propose a review of the mechanisms of action involved in cancer immunology, the response evaluation of immunotherapies, and its toxicity profile, as well as a summary of the main clinical trials that led to the adoption of these new drugs for melanoma treatment.